Estudo sobre a saúde de crianças usuárias de um serviço de saúde mental infantil: a história de Chapeuzinho Amarelo - Lena, Marisangela Spolaôr (2012)
Little Yellow Riding Hood, character in the book of the same name by Chico Buarque, tells the story of the girl who, from their physical and psychological apparatuses, managed to turn the "LO-BO" (wolf in portuguese), of whom she had much fear, in BO-LO (cake in portuguese). In this direction, it is thought that, by knowing the health of children and these 'apparatuses', one can think of better interventions for their welfare. The health of the child, both physical and mental, has been a topic of significant importance in worldwide research, as it is known that a healthy child is more likely to become a healthy adult. This work is linked to a larger project, which aims to apply an intervention in terms of a therapeutic environment in a children s CAPS (Psychosocial Care Center) of Santa Maria-RS (PROCONVIVE, announcement PPSUS/FAPERGS 002/2009 n° of process 0900982). Meanwhile, it was detected the need for an evaluation of data about the children's health, since this may not be always provided to them by the service. This assessment was aimed at knowing the health situation of the children through general health data, evaluation of stress - physical, psychological, psychological with depressive components and psycho-physiological, beyond the data on their emotional functioning. For this, we used a general data questionnaire, the Child Stress Scale (ESI) and the Test of Fables. The evaluation was made in 31 children attending the service, with ages between 4 and 12 years. This study was characterized a descriptive and correlational. The data were analyzed by descriptive and inferential statistics. The calculations were performed using SPSS 13.0. The sample comprised 32.2% of girls (N = 10) and 66.7% of boys (N = 21), with a mean age of 9.39 years. Among the findings, stands out the fact that 80.6% of the children are using at least one medication, being, in its majority, psychiatric medication. Moreover, it is emphasized the fact that 63.2% of the children showed symptoms of stress, and most of them were in alert phase. Of these, 73.7% presented psychological stress with depressive component. Noteworthy is also the fact that 41.6% of the boys exhibit stress, while this data for girls is 85.8%. In regard to emotional functioning, the children showed, in most cases, less primitive defenses and the content of fables used, proved to be adapted. It stands out, in this way, the importance of evaluations of differential diagnosis and assessment of protective factors in considering health promotion and prevention for these children.